Teacher Work Discipline at Vocational School of Applied Techno Aviation Makassar - Ramadhani, Winda Hasrianita; Akib, Haedar; Hasyim, Nasaruddin (Pendidikan Administrasi Perkantoran, UNM, 2025)
This study aims to describe teachers’ work discipline at Makassar Applied Techno Aviation Vocational School. The research serves as a basis for strengthening teacher discipline to build a conducive learning environment and to assess teachers’ professionalism in carrying out their duties. Teacher discipline is closely linked to the quality of learning and character formation of students, making a deeper understanding of this aspect essential. Data were collected through interviews, observations, and documentation, then analyzed through data condensation, data presentation, and conclusion drawing. The results show that teacher discipline at Makassar Applied Techno Aviation Vocational School varies across several indicators. First, compliance with regulations is considered less optimal. Some teachers are not consistently punctual or fail to conduct learning activities according to the set schedule. Attendance and adherence to school policies still require improvement. Second, awareness in performing duties is categorized as good. Teachers understand and carry out the main stages of teaching, including planning, implementation, and evaluation, in line with their professional responsibilities to educate, guide, train, assess, and evaluate students. Third, responsibility is also good. Teachers not only focus on academic aspects but also emphasize character education by strengthening social values. Lesson preparation, teaching implementation, and evaluation are conducted through structured modules and semester assessments. Fourth, exemplary behavior is rated good. Teachers act as role models by communicating politely, being fair and honest in grading, and inspiring students through shared experiences and morning assembly guidance.